Validating Eaton's Hypothesis: Cubane as a Benzene Bioisostere. Issue 11 (5th February 2016) - Chalmers, Benjamin A.; Xing, Hui; Houston, Sevan; Clark, Charlotte; Ghassabian, Sussan; Kuo, Andy; Cao, Benjamin; Reitsma, Andrea; Murray, Cody‐Ellen P.; Stok, Jeanette E.; Boyle, Glen M.; Pierce, Carly J.; et al.
Abstract: Pharmaceutical and agrochemical discovery programs are under considerable pressure to meet increasing global demand and thus require constant innovation. Classical hydrocarbon scaffolds have long assisted in bringing new molecules to the market place, but an obvious omission is that of the Platonic solid cubane. Eaton, however, suggested that this molecule has the potential to act as a benzene bioisostere. Herein, we report the validation of Eaton's hypothesis with cubane derivatives of five molecules that are used clinically or as agrochemicals. Two cubane analogues showed increased bioactivity compared to their benzene counterparts whereas two further analogues displayed equal bioactivity, and the fifth one demonstrated only partial efficacy. Ramifications from this study are best realized by reflecting on the number of bioactive molecules that contain a benzene ring. Substitution with the cubane scaffold where possible could revitalize these systems, and thus expedite much needed lead candidate identification. Abstract : Over 25 years ago, Eaton proposed that cubane could act as a benzene bioisostere. This hypothesis has now been confirmed with the synthesis and evaluation of cubane derivatives of five biologically important molecules: Two cubane analogues showed increased bioactivity compared to their benzene counterparts whereas two further analogues were of equal bioactivity.